2005
DOI: 10.1158/0008-5472.can-04-1532
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Expression Signature for Relapse of Primary Wilms Tumors

Abstract: Anaplastic histology and metastasis are each associated with higher relapse and mortality rates in Wilms tumor patients. However, not all anaplastic tumors relapse and some nonanaplastic tumors relapse unexpectedly. To identify more accurate early prognostic indicators, we analyzed expression of 4,900 cancer-related genes in 26 primary Wilms tumors. This analysis revealed that expression of a set of four genes predicts future relapse of primary Wilms tumors with high accuracy, independent of anaplasia. Random … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 44 publications
2
43
0
2
Order By: Relevance
“…C/EBPb also functions as a prosurvival factor in myc/Ras transformed macrophages in vitro (Wessells et al, 2004) and in Wilms tumor cells (Li et al, 2005). In an attempt to characterize the in vitro role of C/EBPb in keratinocytes survival, we previously treated primary keratinocytes isolated from C/EBPb À/À and wild-type mice with various carcinogens or transfected/infected these primary Figure 1 Targeted conditional mutation of the C/EBPb gene in mice.…”
mentioning
confidence: 99%
“…C/EBPb also functions as a prosurvival factor in myc/Ras transformed macrophages in vitro (Wessells et al, 2004) and in Wilms tumor cells (Li et al, 2005). In an attempt to characterize the in vitro role of C/EBPb in keratinocytes survival, we previously treated primary keratinocytes isolated from C/EBPb À/À and wild-type mice with various carcinogens or transfected/infected these primary Figure 1 Targeted conditional mutation of the C/EBPb gene in mice.…”
mentioning
confidence: 99%
“…Approximately 15-20% of cases of Wilms tumour relapse, more frequently within the first 2-5 years following the primary diagnosis; in these cases, the risk of recurrence is mainly related to the morphological and molecular features of the previous tumour [12,8,18,7,14].…”
Section: Discussionmentioning
confidence: 99%
“…The association of chemotherapy and radiotherapy to radical nephrectomy has increased the overall survival rate up to 85-90% [3,6];however, in spite of these therapeutic improvements, tumour relapses in a subset of patients (15-20%) [12].Numerous studies have demonstrated that the risk of recurrence can be associated to different features such as histological tumour pattern and loss of heterozygosis (LOH) at 1p and/or 16q, as well as gain of chromosome 1 and other recently described alterations [8,18,7,14]. The recurrence risk is greater within the first 2 years after primary diagnosis (in these patients the percentage of survival approximaly ranges from 24% to 43%) but late relapses have occasionally been reported [1,10].…”
Section: Introductionmentioning
confidence: 99%
“…C/EBPb is expressed in many tissues, including epidermis (Maytin and Habener, 1998;Oh and Smart, 1998) where it plays a role in the early stages of stratified squamous differentiation (Zhu et al, 1999). Recent studies have identified a role for C/EBPb in tumor development (Zhu et al, 2002), senescence (Sebastian et al, 2005), cell survival (Buck et al, 2001;Zhu et al, 2002;Wessells et al, 2004;Li et al, 2005) and cellular transformation (Zhu et al, 2002). In terms of cell transformation, C/EBPb can cooperate with Ras12V to transform NIH3T3 cells (Zhu et al, 1999) and more recently, it has been shown that cell-cycledependent phosphorylation of C/EBPb on Ser64 and Thr189 is required to promote Ras-induced transformation of NIH3T3 cells (Shuman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…C/EBPb also has a prosurvival/antiapoptosis function in CCl 4 -treated hepatic stellate cells (Buck et al, 2001). In Wilms' tumors, or nephroblastomas, C/EBPb is expressed at high levels in relapsing and metastatic tumors and blocking C/EBPb expression in a Wilms' tumor cell line results in spontaneous apoptosis (Li et al, 2005). Increased expression of C/EBPb is associated with human breast, colorectal and ovarian tumorigenesis (Sundfeldt et al, 1999;Rask et al, 2000;Bundy and Sealy, 2003).…”
Section: Introductionmentioning
confidence: 99%